Análisis sobre las limitaciones y oportunidades comerciales y de cooperación entre el Ecuador y Arabia Saudita - Burgos González, Bernardo Javier (2021)
The present paper performs an analysis of the reality of Ecuador and Saudi Arabia, makes a review of the flows in the import and export sectors, to know which are the products that move with the higher volume in order to determine the interests of each country in their business activities. It also makes a review of the cooperation activities of the Saudi Government in order to determine if it is possible that Ecuador can access the flows that for this reason that country grants to States in need. In the same way, it analyzes the commercial and investment opportunities that Ecuador offers and those that can emanate from the relationship between both States, as well as the existing limitations in Ecuador and that can influence in one way or another in attracting investment Saudi.